The Immune Monitoring for Operationally Tolerant Recipients Following a Regulatory T cell-based Cell Therapy. (July 2018) - Goto, Ryoichi; Zaitsu, Masaaki; Nagatsu, Akihisa; Emoto, Shin; Fukasaku, Yasutomo; Ganchiku, Yoshikazu; Watanabe, Masaaki; Oura, Tetsu; Ota, Minoru; Suzuki, Tomomi; Taketomi, Akinobu; Shimamura, Tsuyoshi; et al.
Abstract : Background and Aim: We have firstly demonstrated that regulatory T cell (Treg)-enriched cell therapy efficiently promotes an operational tolerance in 7 of 10 cases of living donor liver transplantation (LT). To identify the tolerant immune status and immunological characteristics of the patients following a cell therapy, we evaluated the immune profiles for a total of 5 years including 3.5 years of completely off IS. Methods: PBMCs were collected at pre- and post-transplant periods (7, 14 days, 1, 3, 6 months and annually) from the patients including 7 patients who successfully weaned off IS ( off IS group ) and 3 patients who were unable to be completely off IS due to a rejection ( on IS group ). Immunological assays including lymphocyte subset analysis (FCM) and allo-immune responses (IFNg ELISPOT and MLR) were performed. Results: The dynamic immune profile showed that the anti-donor reactivity was occasionally observed without histologic evidence of rejection in a tolerant case. Meanwhile IFNg ELISpot and cell proliferation assays displayed a donor-specific hyporesponsiveness at long-term; 5 (2-6) years post-LDLT in all patients although the slightly higher frequencies of anti-donor CD4 + T cell reactivity were found in on IS group . Also an increase in the percentage of CD4 + Foxp3 + Tregs during early periods was observed in off IS group (n=7, d7, d14 and d28 post-LT vs. pre-LT, p<0.05, paired T test). Interestingly such phenomenon was found at long-term post-LT (15.9% in off IS vs. 6.47% in on IS ). Furthermore, CD4 + lymphocytes in the peripheral blood obtained from the patients in on IS group (n=3) at pre- and early duration post-LT, were expressed CD45RA and CD62L (so-called naïve subset, *p<0.05 vs. off IS, Fig. A). In contrast, a significant higher percentage of CD4 + memory T cell, namely central memory (CD45RA - CD62L +, Tcm) population was found in off IS patients (n=7, *p<0.05 vs. on IS, Fig. B). Conclusion: The dynamic profile of immune status after an infusion of Treg-enriched cell products for a long-term revealed that the lymphocytes subset such as CD4 + Treg and Tcm during peri-transplant periods may be associated with an induction of immune tolerance by a cell based treatment. A grant in aid from the Japanese Ministry of Health, Labour and Welfare (22130701). Figure. No caption available.